Vortex-Induced Vibration Predictions of a Circular Cylinder Using an Efficient Pseudo-Time Code-Coupling Approach - Hang Li; Kivanc Ekici (Fluids)
Presented in this work is a harmonic balance (HB)-based pseudo-time code-coupling approach applied to a one-degree-of-freedom vortex-induced vibration (VIV) problem of a circular cylinder in a low-Reynolds-number laminar flow regime. Unlike physical time coupling used in traditional time-accurate methods, this novel approach updates both of the fluid and structure fields by integrating respective HB forms of governing equations in pseudo-time, and then couples the two fields in pseudo-time using a partitioned approach. A separate procedure is adopted to determine the VIV frequency at every code-coupling iteration, which enables the simultaneous convergence of variables of both fields in a single run of the solver. For the cases considered here, lock-in vibrations are predicted over a range of Reynolds numbers, inside and outside the resonant range. The results are verified by a time-accurate method and also validated against earlier experimental data, demonstrating the efficiency and robustness of the pseudo-time code-coupling approach.